2008
DOI: 10.1139/y08-086
|View full text |Cite
|
Sign up to set email alerts
|

Rapid cardiovascular effects of dexamethasone in rabbits with meconium-induced acute lung injury

Abstract: Glucocorticoids may improve lung function in newborns with meconium aspiration syndrome (MAS), but information on the acute side effects of glucocorticoids in infants is limited. In this study using a rabbit model of MAS, we addressed the hypothesis that systemic administration of dexamethasone causes acute cardiovascular changes. Adult rabbits were treated with 2 intravenous doses of dexamethasone (0.5 mg/kg each) or saline at 0.5 h and 2.5 h after intratracheal instillation of human meconium or saline. Anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…The importance of the observed effects and relevance of them to the mechanisms of human disease obviously require confirmation with further research, including animal model and clinical studies. However, it is worth noting that this effect of respiratory tract epithelial cell detachment after the exposure to meconium had been previously observed in vitro (13) and in an animal model (13,14) but was thought to be an event secondary to cell death. In our experiments, we showed that cells exposed to meconium in concentrations less than was used by previous investigators (13,14) did indeed detach cells from the surface but that the cells remained viable.…”
Section: Discussionmentioning
confidence: 85%
“…The importance of the observed effects and relevance of them to the mechanisms of human disease obviously require confirmation with further research, including animal model and clinical studies. However, it is worth noting that this effect of respiratory tract epithelial cell detachment after the exposure to meconium had been previously observed in vitro (13) and in an animal model (13,14) but was thought to be an event secondary to cell death. In our experiments, we showed that cells exposed to meconium in concentrations less than was used by previous investigators (13,14) did indeed detach cells from the surface but that the cells remained viable.…”
Section: Discussionmentioning
confidence: 85%
“…Although the acute cardiovascular changes may be critical for neonates with meconium-induced lung injury, the side effects of repetitive GCs administration in MAS have not been investigated yet in a clinical study. In a rabbit model of MAS, the slow intravenous administration of one dose, but especially of two doses of dexamethasone, was associated with acute changes of blood pressure, heart rate and heart rate variability within 5 h of treatment [52, 54]. A detailed analysis of cardiovascular changes showed increased blood pressure, decreased heart rate, increased heart rate variability and a higher occurrence of cardiac arrhythmias particularly during and immediately after dexamethasone administration, while decreased heart rate and increased heart rate variability were observed until the end of the observation period (i.e.…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…A detailed analysis of cardiovascular changes showed increased blood pressure, decreased heart rate, increased heart rate variability and a higher occurrence of cardiac arrhythmias particularly during and immediately after dexamethasone administration, while decreased heart rate and increased heart rate variability were observed until the end of the observation period (i.e. 5 h after the first dose of dexamethasone) [52, 54]. …”
Section: Glucocorticoidsmentioning
confidence: 99%
“…GCs may exert effects on various cells modulating hormone secretion, neuronal excitability, ion cycling, saccharide metabolism, and other processes within seconds or minutes (24,25). Rapid effects of GCs are presumably responsible for inhibition of airway hyperreactivity (26), as well as for cardiovascular changes (27) or improved respiratory parameters (28,29) in animals with MAS observed within minutes after GCs administration.…”
Section: Glucocorticoidsmentioning
confidence: 99%